Improvement of bacterial cellulose nonwoven fabrics by physical entrapment of lauryl gallate oligomers - Song, J. (2020)
The present study aimed to improve the properties of bacterial cellulose nonwoven fabrics by physical entrapment of lauryl gallate oligomers. The lauryl gallate oligomerization process was conducted by laccase-mediated oligomerization. Lauryl gallate was chemically confirmed by matrix-assisted laser desorption/ionization with time-of-flight analyses. The oligomerization conditions were controlled considering the surface properties (water contact angle, surface energy, and water absorption time) of bacterial cellulose nonwoven fabrics. The controlled oligomerization conditions were 160U/mL of laccase and 20mM lauryl gallate. After bacterial cellulose was treated by the physical entrapment of lauryl gallate oligomers, X-ray photoelectron spectroscopy analysis showed that the N1 atomic composition (%) of bacterial cellulose increased from 0.78% to 4.32%. This indicates that the lauryl gallate oligomer molecules were introduced into the bacterial cellulose nanofiber structure. In addition, the water contact angle was measured after washing the bacterial cellulose nonwoven fabric treated by the physical entrapment of lauryl gallate oligomers for 180 minutes, and it was found to maintain a water contact angle of 88°. The durability of bacterial cellulose nonwoven fabric treated by the physical entrapment of lauryl gallate oligomers was confirmed by measuring the tensile strength after wetting and dimensional stability. As a result, the tensile strength after wetting was about five times higher and the dimensional stability was three times higher than that of untreated bacterial cellulose nonwoven fabric.